Effect of a sugar palm fiber and pineapple leaf fiber reinforcement in a polyester matrix on flexural strength and macrostructural characteristics - Wawan Trisnadi Putra; Rizal Arifin; Kuntang Winangun; Fadelan Fadelan; Rangga Ardana Saputra (Politeknik Negeri Lhokseumawe, 2026)
The utilization of natural fiber-based composites has emerged as a promising alternative to synthetic materials because of their lightweight, high strength, and eco-friendly characteristics. This research investigates the influence of combining sugar palm fiber and pineapple leaf fiber on the flexural strength and macrostructural characteristics of polyester-matrix composites. Specimens were fabricated using the hand lay-up press technique, while flexural strength testing followed the ASTM D-790 standard. Macrostructural analysis was performed using a macro lens to evaluate fiber distribution, void presence, and delamination. The results confirmed that fiber composition significantly affected both mechanical and structural properties. Among all specimens, the pineapple-fiber-dominant composite (Specimen 5) achieved the highest flexural strength of 80 MPa, whereas the specimen with higher sugar palm fiber content (Specimen 3) showed the lowest value of 59.4 MPa. Improved performance was strongly associated with uniform fiber distribution, effective interfacial bonding, and reduced voids. Overall, the findings highlight the considerable potential of natural fibers as reinforcements for producing strong, durable, and sustainable composite materials.